Stochastic discretized learning-based weak estimation: a novel estimation method for non-stationary environments. (December 2016) - Yazidi, Anis; Oommen, B. John; Horn, Geir; Granmo, Ole-Christoffer
Abstract: The task of designing estimators that are able to track time-varying distributions has found promising applications in many real-life problems. Existing approaches resort to sliding windows that track changes by discarding old observations. In this paper, we report a novel estimator referred to as the Stochastic Discretized Weak Estimator (SDWE), that is based on the principles of discretized Learning Automata (LA). In brief, the estimator is able to estimate the parameters of a time varying binomial distribution using finite memory. The estimator tracks changes in the distribution by operating a controlled random walk in a discretized probability space. The steps of the estimator are discretized so that the updates are done in jumps, and thus the convergence speed is increased. Further, the state transitions are both state-dependent and randomized . As far as we know, such a scheme is both novel and pioneering. The results which have first been proven for binomial distributions have subsequently been extended for the multinomial case, using which they can be applied to any univariate distribution using a histogram-based scheme. The most outstanding and pioneering contribution of our work is that of achieving multinomial estimation without relying on a set of binomial estimators, and where the underlying strategy is truly randomized. Interestingly, the estimator possesses a low computational complexity that is independent of the number of parameters of the multinomial distribution. The generalization of these results for other distributions has also been alluded to. The paper briefly reports conclusive experimental results that prove the ability of the SDWE to cope with non-stationary environments with high adaptation and accuracy. Abstract : Highlights: We present finite-memory estimation techniques for non-stationary environments. These new techniques use the principles of discretized Learning Automata. The results have been tested for many time-varying problems and applications.